Modern needs in health technology assessment: a study of comparative effectiveness - A. V. Pavlysh; A. S. Kolbin; R. A. Gapeshin; S. M. Malyshev (Union of pediatricians of Russia, 2013)
Health technology assessment is a key component of healthcare decision making in most of the developed countries. Comparative effectiveness research as one of the elements of such assessment is becoming increasingly important in recent years. It is based on the effectiveness analysis of health technologies in real clinical practice setting. The authors have analyzed publications dedicated to these issues and showed the main methods of such study, its peculiarities, advantages and disadvantages. It has been revealed that the most frequently used designs of expert analysis are observational and pragmatic randomized studies. The main recommendations on analyzing comparative effectiveness are given in view of the literary data.